A comparative evaluation of cyclic fatigue resistance of Reciproc Blue, WaveOne Gold and 2Shape nickel-titanium rotary files in different artificial canals - Ankita Grace Lall; Suparna Ganguly Saha; Vijay Alageshan; Parmeet Banga (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this in vitro study was to compare the cyclic fatigue resistance (CFR) of continuous rotation file systems (2Shape) and two reciprocating file systems (Reciproc Blue [RB] and WaveOne Gold [WOG]) in canals with different angulations. Materials and Method: Thirty files each of 2Shape (25, 0.06), RB R25 (25/0.08) and WOG Primary (25/0.07) were included in this study. All the instruments were used according to the manufacturers instructions in an endodontic fatigue testing block with three artificial grooves simulating root canals having angulations of 45°, 60°, and 90°. The files were allowed to rotate in the grooves, until fracture occurred and the time to fracture was recorded in seconds using digital chronometer. The data were analyzed statistically using one-way ANOVA followed by post hoc Tukey test. Results: The reciprocating file systems RB showed significantly higher CFR at all angles of curvature, i.e., 45°, 60°, and 90° (P < 0.05). Conclusions: Within the limitations of the present in vitro study, it may be concluded that RB tends to be more resistant to fracture in canals with a gentle curvature as well as may be more suited in canals with sharp and acute curvatures.